The annual business plan and the recruitment & selection process of Chevron Bangladesh Ltd. - Khan, Mashruk Zaman (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.